KADAR HEMOGLOBIN DAN PREVALENSI ANEMIA PADA IBU LAKTASI YANG BEKERJA DAN YANG TIDAK BEKERJA - Rahayu Astuti; Agustin Syamsianah (JURNAL LITBANG, 2005)
Background : Nutritional anemia among lactating mothers is the one of nutritionalproblem in Indonesia , indicated by the decreasing of hemoglobin level. Lactating mothers can get the nutritional anemia because of blood losses on partus. Objective : to discover hemoglobin level and anemia prevalence on lactating working mothers and lactating non working mothers. Method : this research design is analytical research with cross sectional approach. The research location is in